虞姬形象的叙事演变研究 = A study of the narrative adaption and transformation of the character Yu Ji - 张玉佳 Chong, Yu Jia (2017)
“霸王别姬”的故事流传千年，至今在文学界里还不时成为文人墨客创作的题材，这段千古佳话在不同文人的笔下，呈现出五彩缤纷的火花。虞姬纵为女主角，但关于她的史料极少，再加上她的故事离不开项羽，却被项羽的光芒给掩盖，因而鲜少被提及和进行独立研究。正因虞姬的史料不多，就留给文人无限的想象空间，去刻画虞姬这个人物形象，每个文本所呈现的虞姬不尽相同，为虞姬形象增添了不少色彩。此篇论文旨在以虞姬的角度，细读明传奇《千金记》、京剧《霸王别姬》、张爱玲小说《霸王别姬》以及莫言和王树增联合编写的同名话剧，对不同时期的“霸王别姬”故事进行梳理，从中分析虞姬的形象和性格、虞姬和项羽的关系，以及虞姬自刎的故事。在第四章将以创作因素、时代和社会因素，以及文体因素，以探讨各文本呈现方式的异同和叙事演变的原因。The story of “Farewell my Concubine” has spread for thousand years, and is still a popular theme in classical dramatic narratives. The different interpretations of this eternal story is a fascinating phenomenon. Although Yu Ji is the main female character, historical information on her is scanty, and she is often outshone by Xiang Yu and thus, she is rarely studied as a main topic. This paper investigates four texts related to the story of Yu Ji, namely, the Ming Drama Qian Jin Ji, Peking Opera Farewell my Concubine, the fiction by Eileen Chang with similar title, and the modern stage play written by the renowned Nobel winner Mo Yan and Wang ShuZeng. Different representation of Yu Ji and her relationship with Xiang Yu in different texts are examined in detail. Finally, creative motive, historical background and impact of genre are examined to stipulate how this story evolved through time.